Potencial de eutrofização de bacia hidrográfica do brejo paraibano em função do uso e coberta do solo - Pereira, Maria Cristina Santos (2017)
Phosphorus is limiting nutrient to the eutrophication process, therefore, the quantification of its available and potentially available contents in water and sediment, are useful tools to verify the susceptibility to eutrophication. In this context, the objective of this work was to characterize physicochemically the water and surface sediment of the Canto River, Areia PB, quantifying the total phosphorus and its different fractions at the sediment-water interface. The work was carried out in the River do Canto Hydrographic Basin (BHRC), a mesoregion of the Agreste Paraibano, Northeast of Brazil, composed of six sub-basins, of which three were selected, due to the greater number of land use and occupation classes . In these sub-basins a sampling point of 26 points was used to collect water and sediment, in which samples were taken during the period of November and December of 2014. The variables measured in the water were pH, dissolved oxygen, turbidity and total phosphorus, the latter being used to calculate the Trophic State Index (EIT). For the analysis of the sediment, the surface layer of 5 cm was used, in which pH, Eh, granulometry, carbon and organic matter, iron, aluminum and calcium contents were measured, as well as the forms of phosphorus: soluble, total, organic , inorganic, non-apathetic and apathetic. The results obtained were analyzed through the Pearson correlation and Principal Component Analysis (PCA). The results indicate the following order of susceptibility of the reservoirs to eutrophication: sub-basin 3> sub-basin 1> sub-basin 4. In sub-basin 3, 50% of the reservoirs are already eutrophicated. In sub-basin 1: 5.5; 11.1 and 77.8%, respectively, were classified as eutrophic, mesotrophic and oligotrophic. All the ecosystems of sub-basin 4 are oligotrophic, with emphasis on the Rio do Canto dam, located at the lower boundary of the BHRC, which, due to the influence of the tributaries as well as the rooted macrophytes bank, has a lower phosphorus load. BHRC water was naturally acidic, with low dissolved oxygen content at some points sampled and high phosphorus content, with the following descending order of water quality: sub-basin 4 <sub-basin 1 <sub- basin 3. The areas occupied by cane fields, as well as those of exposed soil contributed to decrease water quality. The results of the analysis of the superficial sediment indicated xv predominance of coarse sediments, which was classified as organic, slightly acid and with potential of oxireduction located in the range that allows the reduction of iron ions. However, correlation of these classes with pH and Eh, in this sense, changes that promote changes in these potentials and mainly in the pH, are not influenced by the classes of use and occupation of the soil, can release phosphorus by accelerating the process of eutrophication. The levels of bioavailable phosphorus in the sediment were high, so it can be inferred that even if all the external phosphorus loads are canceled, the reservoirs are still susceptible to the eutrophication process as a consequence of the internal charge of this nutrient.